2015
DOI: 10.1590/s1984-82502015000300015
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the anti-inflammatory and anti-apoptotic effects of crocin against gastric ischemia-reperfusion injury in rats

Abstract: The aim of the present study was to investigate the protective effect of crocin on gastric mucosal lesions caused by ischemia-reperfusion (I/R) injury in rats. Thirty-two male rats were randomly divided into sham, I/R, I/R + crocin pretreatment and crocin alone groups. To induce I/R lesions, the celiac artery was clamped for 30 min, and the clamp was then removed to allow reperfusion for 3 h. Crocin-pretreated rats received crocin (15 mg/kg, i.p.) 30 min prior to the induction of I/R injury. Samples of gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
0
17
0
2
Order By: Relevance
“…Previous studies have shown that microscopic changes such numerous erosions, spillage of superficial cells, necrosis, hemorrhages in the mucosal layers, inflammation, and neutrophil aggregation occur in gastric tissue with the I/R procedure, and that administration of gallic acid reduces these symptoms 28 . In our study, metyrosine had a protective effect on gastric tissue by preventing histopathological symptoms such as necrosis, hemorrhage, and edema that developed in the stomach due to I/R injury.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Previous studies have shown that microscopic changes such numerous erosions, spillage of superficial cells, necrosis, hemorrhages in the mucosal layers, inflammation, and neutrophil aggregation occur in gastric tissue with the I/R procedure, and that administration of gallic acid reduces these symptoms 28 . In our study, metyrosine had a protective effect on gastric tissue by preventing histopathological symptoms such as necrosis, hemorrhage, and edema that developed in the stomach due to I/R injury.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Various pharmacological effects of saffron and its components have been published in some studies, such as antidepressant (Akhondzadeh et al, 2005;Moshiri et al, 2006), Alzheimer's treatment (Akhondzadeh et al, 2010) anticancer (Abdullaev & Espinosa-Aguirre, 2004;Bolhassani, Khavari, & Bathaie, 2014), anti-ischemic on the kidneys (Hosseinzadeh & Nassiri-Asl, 2013), brain (Naghizadeh, Mansouri, Ghorbanzadeh, Farbood, & Sarkaki, 2013), heart (Bharti, Golechha, Kumari, Siddiqui, & Arya, 2012), and muscle (Hosseinzadeh, Modaghegh, & Saffari, 2009). In addition, analgesic and antiinflammatory effects have been reported in various studies (Mard, Nikraftar, Farbood, & Mansouri, 2015;Nasri, Hosseini, Sahraei, & Zardooz, 2011;Rezaee & Hosseinzadeh, 2013).…”
mentioning
confidence: 95%
“…L E 1 Modulatory effects of crocin on inflammatory diseases Decreasing the mRNA expression of IFN-γ, TNFα, IL-1β, COX-2, NF-κB Mard et al (2015). …”
mentioning
confidence: 99%